Władysław Marek Kolasa, Grzegorz Nieć, Bibliografia historii prasy polskiego ruchu ludowego, Warszawa 2012 - Grażyna Gzella (Toruńskie Studia Bibliologiczne, 2013)
Review of a book presenting current research into the history of Polish popular press. The book is an attempt to describe and evaluate research in the field. It also draws attention to significant needs and deficiencies in this area.